1990
DOI: 10.1017/s004740450001455x
|View full text |Cite
|
Sign up to set email alerts
|

The organization of repair in classroom talk

Abstract: This article is a conversation-analytic investigation of the forms of organization that allow specific items of classroom discourse -words, phrases, up to whole turns at talk -to be altered by subsequent items. Central to the article is an analytic distinction between self-correction and other-correction, that is, between repair sequences in which the speaker of the initial item (the "trouble source") makes the correction and instances in which this is performed by one of her or his interlocutors (cf. Jefferso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(150 citation statements)
references
References 8 publications
7
132
0
11
Order By: Relevance
“…From the CA toolbox we can refer, for example, to the teacher's using pauses and intonation to mark important information (lines 1, 16) and for the transition from one concept to another (lines 15-16), to her initiating a repair sequence (line 12) and to her completing learner-performed correction (line 5, see also McHoul, 1990), and to the aspects of institutional talk regarding the organization of turns in the classroom (cf. Mchoul, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…From the CA toolbox we can refer, for example, to the teacher's using pauses and intonation to mark important information (lines 1, 16) and for the transition from one concept to another (lines 15-16), to her initiating a repair sequence (line 12) and to her completing learner-performed correction (line 5, see also McHoul, 1990), and to the aspects of institutional talk regarding the organization of turns in the classroom (cf. Mchoul, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, knowing (K+) speakers can simply initiate talk concerning the matter at hand, thus launching a sequence, finding a warrant for this conduct by projecting their recipients to be in a relatively unknowing (K−) position." (Heritage, 2012, p. 33) The imbalance territories of information or knowledge state (K+ and K−) was also noticed by McHoul (1990) as a key driving element that motivate sequence organizations in a classroom. In McHoul's study, the focus is on the analysis of how teachers organize repair trajectories to achieve a pedagogical goal of initiating students' self-correction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on classroom interaction, most of them have narrowed their focuses down to the studies of particular action types (see for example Brown, 1994;Markee, 1995;Suter, 2001;Morell, 2007), and particular sequences structures in the classrooms (e.g. McHoul, 1990; Lee, 2007Lee, , 2008. What new and interesting for this field of classroom interactional research is an understanding of the more complex processes through which a teacher and students conjointly produce, interpret and negotiate meanings of actions being done, which manifests itself in the extended structures of interactional sequences or sequences of sequences rather than a building block of initiation−response−evaluation (IRE) sequences.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely shown that the characteristic sequence of tripartite dialogic structure that dominates instructional discourse consists of an initiation, a response, and feedback (IRF) [13] [14]. In general, the basic three part sequence entails: (1) initiation of a known-answer question by the teacher, (2) a student response to that question and (3) teacher feedback or evaluation of that response, where responsibility for management of the interaction rests with the teacher throughout [1] [15].…”
Section: The Irf Dialoguementioning
confidence: 99%